Analisis Pengaruh Investasi dan Pengeluaran Pemerintah Terhadap Ketimpangan Pendapatan di Kota Jayapura - Agustina Sanggrangbano; Tessalonika Florenchia Larawo (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2025)
The influence of investment and government spending on income inequality in Jayapura City from 2016 to 2023. The research method used was multiple linear regression. The analysis results showed that investment actually has a significant negative impact on income inequality. This finding indicates that the benefits of investment are felt more by high-income groups, thus widening the gap between the rich and the poor. Meanwhile, low-income groups experience a wider gap due to the inequity in the allocation of investment benefits. On the other hand, government spending has been shown to make a significant positive contribution to increasing the income of low- and middle-income groups. Through social programs and appropriate budget allocation, government spending helps improve the standard of living of these groups and thus can reduce income inequality. These findings suggest that inclusive and welfare-oriented government policies can be an effective tool in addressing inequality issues. This study highlights the importance of the government's role in formulating policies that not only encourage investment but also ensure that the benefits of such investment are felt by all levels of society. Therefore, increasing budget allocations for social programs and equitable infrastructure development is essential to create a better balance in income inequality. Keywords: Investment, Government Spending, and Income Inequality